Number of hospital contacts with alcohol problems predicts later risk of alcoholic liver cirrhosis. Issue 4 (June 2019) - Askgaard, Gro; Tolstrup, Janne S.; Kjær, Mette S.; Leon, David A.
Aims: Alcoholic liver cirrhosis is usually preceded by years of heavy drinking. We investigated whether the risk of alcoholic liver cirrhosis increases as the number of hospital contacts with alcohol problems goes up. Methods: This was a supplementary analysis on a nationwide register-based cohort study. All patients in Denmark with an initial hospital contact with alcohol problems (alcohol intoxication, harmful alcohol use or alcohol dependence) 1998–2002, free of liver disease, were followed for diagnosis of alcoholic liver cirrhosis. The number of subsequent hospital contacts with alcohol problems was estimated as a time-dependent variable for each patient. Results: In all, 36, 044 hospital patients with an initial hospital contact with alcohol problems were included. These patients had 301, 525 subsequent hospital contacts with alcohol problems. Risk of alcoholic liver cirrhosis increased ( p < 0.0001) with number of alcohol hospital contacts in both men and women for up to nine contacts. Conclusions: The number of prior hospital contacts with alcohol problems might provide clinicians with a helpful metric in deciding whether to offer preventive interventions for alcoholic liver cirrhosis.